Dependence of reactions of the external respiratory system in athletes on the orientation of the training process - S. M. Kanyhina; M. S. Potapenko; L. O. Kurilets (Zaporozhye State Medical University, 2021)
Issues of improving the functional training (different orientation of the training process) of athletes due the development of the respiratory system, including the respiratory system, as well as increasing the body's resistance to hypoxic stress remain extremely relevant at the present stage of sport development. The aim of the study is to investigate the peculiarities of the reaction of the external respiratory system in athletes, depending on the orientation of the training process. Materials and methods. The study involved 104 athletes (84 men and 20 women) skill level from CMS to IMS: 63 - athletes, who developed mainly endurance quality (triathletes, swimmers, long-distance runners, rowing), 31 - strength quality (weightlifters, powerlifting, weightlifting), 10 - speed quality (runners sprinters). The mean age of the athletes under study was 21.75 ± 3.32 years. Among them there are international masters of sports (IMS) - 2 athletes, masters of sports (MS) - 25, candidates for master of sports - 48, athletes of 1 degree - 29. Computer spirometric examination was performed for all athletes using the spirographic complex "Spirocom" produced by LLC "KHAI-Medica" in Kharkiv in accordance with existing recommendations. Research results. Analysis of computer spirometry showed, that athletes, who developed the quality of strength had 18.2 % (P = 0.014) greater vital capacity of the lungs, due to the predominance of respiratory volume by 29.9 % (P = 0.017) and by 42.1 % (P = 0.001) inspiratory reserve volume, but less by 22.4 % (P = 0.019) expiratory reserve volume, than athletes, who improved the quality of endurance. Athletes, who developed the quality of endurance in contrast to athletes, who improved the quality of speed had a higher forced vital capacity of the lungs by 14.9 % (P = 0.031), due to the predominance of a inspiratory reserve volume by 9.8 % (P = 0.049) and expiratory reserve volume by 28.5 % (P = 0.044). Athletes, who improved the quality of speed had lower vital capacity of the lungs by 26.1 % (P = 0.003), forced vital capacity of the lungs by 20.2 % (P = 0.016), due to a decrease of inspiratory reserve volume by 34.2 % (P = 0.008), than athletes, who improved the quality of strength. Athletes, who developed the quality of speed, had greater resistance to air flow in the bronchi of small caliber in the exhalation phase, as evidenced by a lower rate of forced expiratory volume1 by 21.1 % (P = 0.015), the volume of forced expiratory to reach the peak expiratory flow by 30.2 % (P = 0.016), MEF 75 by 22.9 % (P = 0.036), FEF 75-85 by 22.8 % (P = 0.035), than athletes, who developed the quality of strength. Conclusions Athletes, who have developed a quality of strength have a greater vital capacity of the lungs, due to the predominance of respiratory volume and inspiratory reserve volume, but less expiratory reserve volume, than in athletes, who improved the quality of endurance. Athletes, who developed endurance quality, in contrast to athletes, who improved the quality of speed, have a higher forced vital capacity of the lungs, due to the predominance of inspiratory and expiratory reserve volumes. The function of external respiration of athletes, who improved the quality of speed is characterized by lower vital capacity of the lungs, forced vital capacity of the lungs, due to reduced inspiratory reserve volume, and greater resistance to airflow in the bronchi of small caliber in the expiratory phase, than in athletes, who developed the quality of strength.